Excitation Dynamics of a Low Bandgap Silicon-bridged Dithiophene Copolymer and its Composites with Fullerenes - Choulis, Stelios A.; Othonos, Andreas S.; Neophytou, Marios; Itskos, Grigorios (My University, 2012)
We report on excitation dynamics in pristine and bulk heterojunction films of the low bandgap silicon-bridged dithiophene copolymer poly[(4,4′-bis(2- ethylhexyl)dithieno[3,2-b:2′, 3′-d]silole)-2,6-diyl-alt-(4,7-bis(2- thienyl)-2,1,3-benzothiadiazole)-5,5′-diyl] with methanofullerene derivatives. The combination of ultrafast transient transmission and photoluminescence allows us to probe the relaxation of both exciton and polaron states in a relatively wide spectral and temporal range. Measurements reveal that the majority of excitations undergo ultrashort non-radiative relaxation while a small fraction of the photoexcited species decays slowly within hundreds of ps. In the blend films, significantly longer decays are observed suggesting the presence of long lived holes and/or charged-transfer type of excitons. © 2012 American Institute of Physics.
Keywords: Polymer Solar Cell; Bulk Heterojunction; Organic Photovoltaic